If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 + -8x = 3x + -7(6x + 8) Reorder the terms: 37 + -8x = 3x + -7(8 + 6x) 37 + -8x = 3x + (8 * -7 + 6x * -7) 37 + -8x = 3x + (-56 + -42x) Reorder the terms: 37 + -8x = -56 + 3x + -42x Combine like terms: 3x + -42x = -39x 37 + -8x = -56 + -39x Solving 37 + -8x = -56 + -39x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '39x' to each side of the equation. 37 + -8x + 39x = -56 + -39x + 39x Combine like terms: -8x + 39x = 31x 37 + 31x = -56 + -39x + 39x Combine like terms: -39x + 39x = 0 37 + 31x = -56 + 0 37 + 31x = -56 Add '-37' to each side of the equation. 37 + -37 + 31x = -56 + -37 Combine like terms: 37 + -37 = 0 0 + 31x = -56 + -37 31x = -56 + -37 Combine like terms: -56 + -37 = -93 31x = -93 Divide each side by '31'. x = -3 Simplifying x = -3
| -8(3b+2)+(25b-7)=0 | | Y=-2/3(0)+6 | | 1.5r+15=2.2r | | (9-z)(4z+1)=0 | | x/(x+600)=0.55 | | 4x-26-3x=16-30 | | y=5(10.5)+3 | | b-6/3=b+5/2 | | m-2=3m | | 4(r+6)=31+3r | | 1-4a-6a=11 | | (8x-12)=(3x+28) | | -30=6x+4(-x-4) | | 6=-6+4x+2x | | (y+8)=6.333 | | 15+(5-x)=30 | | 5y+2=0.50(10y+4) | | 3y-3+y+53=6y+50-4y | | -4x2/7 | | 4(x+6)=31+3r | | 20+4k=k | | 17/3+6 | | y=6(4)+(-12) | | (6x-14)=(3x+5) | | 3x^2+28x+19=0 | | 3-k-4=3 | | x/(x+600)=0.7 | | x/2+25=50 | | (3+-4)-5= | | 15(x-3)+3x=6(3x+5)-11 | | 7x+w=21y | | -6p+4+p=14 |